Temoporfin improves efficacy of photodynamic therapy in advanced biliary tract carcinoma: A multicenter prospective phase II study. Issue 5 (22nd July 2015) - Wagner, Andrej; Denzer, Ulrike W.; Neureiter, Daniel; Kiesslich, Tobias; Puespoeck, Andreas; Rauws, Erik A.J.; Emmanuel, Klaus; Degenhardt, Nora; Frick, Ulrich; Beuers, Ulrich; Lohse, Ansgar W.; Berr, Frieder; et al.
<x xml:space="preserve">Abstract</x> Photodynamic therapy using porfimer (P‐PDT) improves palliation and survival in nonresectable hilar bile duct cancer. Tumoricidal penetration depth of temoporfin‐PDT (T‐PDT) is twice that of P‐PDT. In a single‐arm phase II study we investigated the safety, efficacy, survival time, and adverse events of T‐PDT compared with previous data on P‐PDT. Twenty‐nine patients (median 71 [range 47‐88] years) with nonresectable hilar bile duct cancer were treated with T‐PDT (median 1 [range 1‐4] sessions) plus stenting and followed up every 3 months. The PDT was well tolerated. In patients with occluded segments at baseline (n = 28) a reopening of a median of 3 (range 1‐7) segments could be achieved: n = 16 local response and n = 11 stable local disease, one progressive disease. Cholestasis and performance significantly improved when impaired at baseline. Time to local tumor progression was a median of 6.5 (2.7‐41.0) months. Overall survival time was a median of 15.4 (range 4.4‐62.4) months. Patients died from tumor progression (55%), cholangitis (18%), pneumonia (7%), hemobilia (7%), esophagus variceal hemorrhage (3%), and vascular diseases (10%). Adverse events were cholangitis (n = 4), liver abscess (n = 2), cholecystitis (n = 2), phototoxic skin (n = 5), and injection site reactions (n = 7). Compared to previous P‐PDT, T‐PDT shows prolonged time to local tumor progression (median 6.5 versus 4.3 months, P < 0.01), fewer PDT treatments needed (median 1 versus 3, P < 0.01), a higher 6‐month survival rate (83% versus 70%, P < 0.01), and a trend for longer overall median survival (15.4 versus 9.3 months, P = 0.72) yet not significantly different. The risk of adverse events is not increased except for (avoidable) subcutaneous phototoxicity at the injection site. Conclusion: Temoporfin‐PDT can safely be delivered to hilar bile duct cancer patients and results in prolonged patency of hilar bile ducts, a trend for longer survival time, and similar palliation as with P‐PDT. (Hepatology 2015;62:1456–1465)